Religious Freedom and Limits of Tolerance - Siti Faridah (Universitas Negeri Semarang, 2018)
Religious freedom is a fundamental human right, enabling individuals to practice their religious beliefs according to their personal beliefs. In Indonesia, a country with rich religious diversity, freedom of religion is guaranteed in the constitution. However, challenges arise in managing and maintaining interfaith harmony and overcoming the boundaries of tolerance. Although the constitution guarantees freedom of religion, there are cases where religious minorities face discrimination or restrictions on practicing their religion. Often times, multiple interpretations of religious teachings and a lack of understanding across religions can generate tension. Governments and society need to work together to promote interfaith dialogue and a deeper understanding of different religious beliefs. The limit of tolerance becomes an important issue in this context. Religious tolerance is an important foundation for social harmony, but it remains a question of where the line should be drawn. Tolerance should not be used as a justification for extremism or intolerance of different views. Therefore, there is a need to develop a clear framework on tolerance limits that respect human rights while preventing the spread of hatred and violence. In order to achieve an inclusive and harmonious society, it is necessary to have a balanced approach between freedom of religion and limits of tolerance. Governments must ensure the protection of the rights of religious minorities, while promoting strong values of tolerance and interfaith dialogue. Collective efforts to overcome differences and understand diverse religious perspectives will help build a more tolerant and united Indonesia.